2009
DOI: 10.1111/j.1365-294x.2009.04118.x
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene glaciation events shape genetic structure across the range of the American lobster, Homarus americanus

Abstract: A north/south discontinuity along the northeastern coast of North America in the genetic structure of the American lobster (Homarus americanus) was detected using a suite of 13 microsatellite loci assessed using spatial analyses. Population genetic data laid over existing data on physiographic changes and sea-surface temperatures were used to reconstruct the Pleistocene distribution of this species. A postglacial northern-edge colonization model best explains the relative genetic homogeneity of the northern re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
43
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(51 citation statements)
references
References 73 publications
8
43
0
Order By: Relevance
“…One recent example is the determination of population structure in H. americanus, the nearest relative of H. gammarus. Kenchington et al (2009) used 13 microsatellites to assess population structure in H. americanus, identifying 2 population clusters, divided into the northern and southern portions of the species' range. Since then, Benestan et al (2015) confirmed this broad-scale divergence using > 8000 neutral single nucleotide polymorphisms, but also discovered robust evidence for IBD and hierarchical fine-scale differentiation.…”
Section: Methodological Power and Resolutionmentioning
confidence: 99%
“…One recent example is the determination of population structure in H. americanus, the nearest relative of H. gammarus. Kenchington et al (2009) used 13 microsatellites to assess population structure in H. americanus, identifying 2 population clusters, divided into the northern and southern portions of the species' range. Since then, Benestan et al (2015) confirmed this broad-scale divergence using > 8000 neutral single nucleotide polymorphisms, but also discovered robust evidence for IBD and hierarchical fine-scale differentiation.…”
Section: Methodological Power and Resolutionmentioning
confidence: 99%
“…Landscape genetic analysis has been increasingly successfully used to identify spatial patterns of genetic structure and possible regions of discontinuous gene flow in both terrestrial and marine studies (Miller et al 2006, Kenchington et al 2009). These analyses are based on statistical procedures that rely primarily on patterns of interindividual genetic and geographical variation (see Manel et al 2003 for a review).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Nova Scotia separates warmer shallow waters in the Gulf of St. Lawrence from the cold waters of the Labrador Current, providing refugia for many marine coastal species (Bousfield and Thomas 1975). The boundaries between these biogeographic provinces are filters to gene flow in many western North Atlantic species, including amphipods (Jones 2005; Kelly et al 2006), polychaetes (Jennings et al 2009), and lobster (Kenchington et al 2009) through limits to larval dispersal, recruitment, adult survival, or adult habitat choice. However, despite the apparent strength of these environmental filters, they are largely invisible to others species such as weakfish (Cordes and Graves 2003), bivalves (Dahlgren et al 2000; Hare and Weinberg 2005; Strasser and Barber 2008), and other gastropods (Collin 2001) (see Wares 2002 for review).…”
Section: Introductionmentioning
confidence: 99%